Corrigendum Supports Therapeutic Contribution of Acupoint Tapping to EFTs' Observed Effects: Response to Spielmans (2021). Issue 2 (February 2022) - Church, Dawson; Kip, Kevin; Stapleton, Peta
Abstract : Abstract: We published a meta-analysis of studies that examined the various components of an evidence-based therapy called emotional freedom techniques (EFTs). EFT uses elements of conventional therapies such as exposure and cognitive processing but includes the unique ingredient of acupoint stimulation using fingertip tapping. Six studies were identified, and three of these met the quality control criteria of the American Psychological Association's Division 12 Task Force for Empirically Validated Therapies. Meta-analysis found that the acupoint component of EFT was not an inert ingredient or inactive placebo but made an active contribution to the therapeutic effects noted in a research literature that now numbers over 100 clinical trials of EFT. Subsequent to publication, errors in the original analysis were identified, primarily incorrect standard deviations. A new analysis was performed by an independent statistician and found slightly greater effects than the original investigation. The results were published as a corrigendum, which was subsequently challenged by Spielmans. Here we examine the critiques of the corrigendum and original article. We find that although they may be of academic interest, they are irrelevant to the central research question of whether the acupoint component of EFT is inert or active. We reaffirm that the evidence clearly validates the contribution made by acupoint tapping to EFT's observed clinical effects.